Firm-level Inefficiency in Post-transition Economies - Valerija Botrić (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
Firms in post-transition economies are frequently considered less efficient than those in more advanced market economies. By relying on the World Bank Enterprise Survey for the year 2019, firm-level technical inefficiency is estimated by the stochastic frontier analysis method for a sample of European post-transition countries. To be precise, the analysis included Albania, Bosnia and Herzegovina, Croatia, Czechia, Estonia, North Macedonia, Poland, Serbia, and Slovenia. Furthermore, the factors contributing to the firm-level inefficiency are explored in a comparative setting. The effects of the international orientation of the firm, foreign ownership, doing business with the government sector, presence of informal competitors, innovation activity, manager experience, and the age of the firm on the technical inefficiency are estimated. Results show that although some factors are common to a subsample of countries, not a single factor is significant in all the analysed economies.
Keywords: D29; L25; 330; firm inefficiency; post-transition economies; stochastic frontier analysis